Hepatitis B virus reactivation and hepatitis in diffuse large B-cell lymphoma patients with resolved hepatitis B receiving rituximab-containing chemotherapy: risk factors and survival - Chen, Kai-Lin (Chin J Cancer, 2015)
INTRODUCTION: Hepatitis B virus (HBV) reactivation has been reported in B-cell lymphoma patients with resolved hepatitis B (hepatitis B surface antigen [HBsAg]-negative and hepatitis B core antibody [HBcAb]-positive). This study aimed to assess HBV reactivation and hepatitis occurrence in diffuse large B-cell lymphoma (DLBCL) patients with resolved hepatitis B receiving rituximab-containing chemotherapy compared with HBsAg-negative/HBcAb-negative patients to identify risk factors for HBV reactivation and hepatitis occurrence and to analyze whether HBV reactivation and hepatitis affect the survival of DLBCL patients with resolved hepatitis B. METHODS: We reviewed the clinical data of 278 patients with DLBCL treated with rituximab-containing therapy between January 2004 and May 2008 at Sun Yat-sen University Cancer Center, China. Predictive factors for HBV reactivation, hepatitis development, and survival were examined by univariate analysis using the chi-square or Fisher’s exact test and by multivariate analysis using the Cox regression model. RESULTS: Among the 278 patients, 165 were HBsAg-negative. Among these 165 patients, 6 (10.9%) of 55 HBcAb-positive (resolved HBV infection) patients experienced HBV reactivation compared with none (0%) of 110 HBcAb-negative patients (P = 0.001). Patients with resolved hepatitis B had a higher hepatitis occurrence rate than HBsAg-negative/HBcAb-negative patients (21.8% vs. 8.2%, P = 0.013). HBcAb positivity and elevated baseline alanine aminotransferase (ALT) levels were independent risk factors for hepatitis. Among the 55 patients with resolved hepatitis B, patients with elevated baseline serum ALT or aspartate aminotransferase (AST) levels were more likely to develop hepatitis than those with normal serum ALT or AST levels (P = 0.037, P = 0.005, respectively). An elevated baseline AST level was an independent risk factor for hepatitis in these patients. Six patients with HBV reactivation recovered after immediate antiviral therapy, and chemotherapy was continued. HBcAb positivity, HBV reactivation, or hepatitis did not negatively affect the survival of DLBCL patients. CONCLUSIONS: DLBCL patients with resolved hepatitis B may have a higher risk of developing HBV reactivation and hepatitis than HBsAg-negative/HBcAb-negative patients. Close monitoring and prompt antiviral therapy are required in these patients.